PENGARUH PELATIHAN, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMP STRADA BUDI LUHUR BEKASI - Mugiani, Natasha Queenta; sudianti, Dian; Narpati, Bintang (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to determine the influence of training, work environment, and work motivation on the performance of teachers at SMP Strada Budi Luhur. The type of research used is quantitative research with a saturated sample, which involves using the entire population as the sample, consisting of 50 teachers at SMP Strada Budi Luhur. The data analysis method used SEM-PLS and the data were processed using SmartPLS 4.0. The results of this study indicate that (1) Training has a positive and significant effect on teacher performance at SMP Strada Budi Luhur, with t-statistic values 2.475 and p-values 0.07. (2) The work environment has a positive and significant effect on the performance of teachers at SMP Strada Budi Luhur with a t-statistic value of 0.121 and p-values 0.049. (3) Work motivation has a positive and significant effect on the performance of teachers at SMP Strada Budi Luhur with a t-statistic value 3.947 and p-values 0.00. (4) Training, work environment, and work motivation simultaneously affect the performance of teachers at SMP Strada Budi Luhur.